2016
DOI: 10.1104/pp.16.01190
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Ubiquitin-Conjugating Enzymes Is Essential for Plant Immunity

Abstract: Of the three classes of enzymes involved in ubiquitination, ubiquitin-conjugating enzymes (E2) have been often incorrectly considered to play merely an auxiliary role in the process, and few E2 enzymes have been investigated in plants. To reveal the role of E2 in plant innate immunity, we identified and cloned 40 tomato genes encoding ubiquitin E2 proteins. Thioester assays indicated that the majority of the genes encode enzymatically active E2. Phylogenetic analysis classified the 40 tomato E2 enzymes into 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 99 publications
2
86
2
Order By: Relevance
“…Significantly, the unique bacterial ubiquitin ligase AvrPtoB, which is a virulence effector encoded by Pseudomonas syringae pv. tomato (Abramovitch, Janjusevic, Stebbins, & Martin, ; Janjusevic, Abramovitch, Martin, & Stebbins, ), specially works with group III E2s for its in planta virulence activity (Zhou et al ., ), suggesting that a given E3 ubiquitin ligase may have preference to distinct E2 ubiquitin‐conjugating enzyme for its intrinsic activity. Thus, the weak ubiquitination rendered by SlSINA3/4/5 in the in vitro ubiquitination assay (Figure a) could be attributable to the intrinsic weak E3 activity or inappropriate E2 used in the assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly, the unique bacterial ubiquitin ligase AvrPtoB, which is a virulence effector encoded by Pseudomonas syringae pv. tomato (Abramovitch, Janjusevic, Stebbins, & Martin, ; Janjusevic, Abramovitch, Martin, & Stebbins, ), specially works with group III E2s for its in planta virulence activity (Zhou et al ., ), suggesting that a given E3 ubiquitin ligase may have preference to distinct E2 ubiquitin‐conjugating enzyme for its intrinsic activity. Thus, the weak ubiquitination rendered by SlSINA3/4/5 in the in vitro ubiquitination assay (Figure a) could be attributable to the intrinsic weak E3 activity or inappropriate E2 used in the assay.…”
Section: Resultsmentioning
confidence: 99%
“…It is logical to hypothesize that the most appropriate combination of E3 with E2 will lead to optimization of ubiquitination process. There are 34 distinct functional E2 found in tomato, and they are classified into 13 groups (Zhou et al ., ). Our results indicated that the SlSINAs only function cooperatively with Group III of tomato E2s (Figure a; Figure S2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As previously reported (Wu et al, 2013), the HYL1-containing D-bodies 303 existed in most cells (~ 84%, Figure 6A, 6B and Supplemental Figure 6A Because MAC3A has considerable sequence difference from MAC3B, we tested if it is a 318 ubiquitin E3 ligase using MBP-MAC3A (Supplemental Figure 5A). We examined the E3 ligase 319 activity in the presence of ubiquitin, the ubiquitin-activating enzyme (E1) SlUBA and the 320 ubiquitin-conjugating enzyme (E2) UBC8 (Zhou et al, 2017). However, MBP-MAC3A 321 displayed only weak activity ( Figure 7B).…”
Section: Mac3a Binds Pri-mirnas In Vivo 274mentioning
confidence: 99%
“…The in vitro ubiquitination assay was performed as described (Zhou et al, 2017) protein modification on MAC3A activity, the recombinant proteins were treated as previously 485 described with modifications (Wang et al, 2015). Briefly, 4 µg MBP, MBP-MAC3A, MBP-486…”
mentioning
confidence: 99%